Journal Writing: Effects on Students’ Writing Proficiency and Student and Teacher Attitudes - Yurekli, Aynur; Afacan, Anita (Register Journal, 2020)
In today’s world, writing is no longer a natural activity, especially for the younger generation. They look upon this activity as too complex, overwhelming and sometimes irrelevant. These attitudes are amplified when having to write in a second language. In EFL tertiary education, the expectations of academic achievement have become far greater than actual student capabilities. This study examined the possibility of using journal writing, both with and without an audience, as a way to address this issue. It is believed that by engaging students in the act of writing without the burden of an academic topic, it will indirectly impact students’ academic performance. Seventy-six undergraduate students in three groups (one control and two experimental) were involved. Data was collected in the form of pre-test and post-test writing, student focus group meetings and an interview with the instructor. From the study, it was found that dialogue journal writing with an audience contributed to an increase in the proficiency level of students, especially in terms of their organizational skills. In addition, students who undertook journal writing expressed gains in self-confidence, and were aware of the role of journal writing in this. Finally, journal writing was found to offer insight to the instructor with regard to what is happening under the surface of a class, and thus better address students’ needs. Keywords: EFL, academic writing, writing proficiency, journal writing